2018
DOI: 10.1093/mnras/sty250
|View full text |Cite
|
Sign up to set email alerts
|

Do L chondrites come from the Gefion family?

Abstract: Ordinary chondrites (H, L, and LL chondrites) are the most common type of meteorites comprising 80 per cent of the meteorites that fall on Earth. The source region of these meteorites in the main asteroid belt has been a basis of considerable debate in the small bodies community. L chondrites have been proposed to come from the Gefion asteroid family, based on dynamical models. We present results from our observational campaign to verify a link between the Gefion asteroid family and L chondrite meteorites. Nea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…However our full sample analysis with the Granvik model offers a 5:2 escape region preference that is possibly significant only at the 1σ-level. This outer belt region, and in particular the Gefion family adjacent to the 5:2 resonance have been proposed as a supply source for the L-chondrite meteorites (Nesvorný et al, 2009), with a recent analysis by McGraw et al (2018) suggesting the Gefion region may be more compositionally diverse. Our analysis is not inconsistent with the 5:2 resonance being a preferred Lchondrite delivery source, but does not offer a strong conclusion.…”
Section: Escape Regions For "H- L- and Ll-chondrite" Near-earth Objmentioning
confidence: 96%
See 1 more Smart Citation
“…However our full sample analysis with the Granvik model offers a 5:2 escape region preference that is possibly significant only at the 1σ-level. This outer belt region, and in particular the Gefion family adjacent to the 5:2 resonance have been proposed as a supply source for the L-chondrite meteorites (Nesvorný et al, 2009), with a recent analysis by McGraw et al (2018) suggesting the Gefion region may be more compositionally diverse. Our analysis is not inconsistent with the 5:2 resonance being a preferred Lchondrite delivery source, but does not offer a strong conclusion.…”
Section: Escape Regions For "H- L- and Ll-chondrite" Near-earth Objmentioning
confidence: 96%
“…Note that iron, stony-iron, and other metal-rich classes account for a comparable total mass of meteorite falls, but these classes are not included in the accounting here nor are they depicted in the cumulative curves of Fig. 15 (See References: Gaffey et al (1992Gaffey et al ( , 1993, Binzel et al (1996), Gaffey and Gilbert (1998), Thomas et al (2010), Vernazza et al (2008Vernazza et al ( , 2014Vernazza et al ( , 2015, Nesvorný et al (2009), Fornasier et al (2015), McGraw et al (2018, Vokrouhlický et al (2017), Granvik and Brown (2018), Bowell et al (1978), Vilas and Smith (1985), Love and Brownlee (1993), Cuk et al (2014), McCord et al (1970, Consolmagno and Drake (1977), Cruikshank et al (1991), Binzel and Xu (1993), Prettyman et al (2012), Sunshine et al (2008), Devogèle et al (2018), Bogard and Johnson (1983), Smith et al (1984) , Polishook et al (2017)).…”
Section: Escape Region Comparison For Near-earth Objects and Meteoritesmentioning
confidence: 99%
“…Nesvorný et al (2009) and Vernazza et al (2014) have proposed the Gefion asteroid family as the source region of L chondrites. But more recent observations by McGraw et al (2018) show that Gefion might have a mixture of H and L chondrites. The Flora family in the inner main belt has been proposed as the source family of the LL chondrites (Vernazza et al 2008(Vernazza et al , 2014.…”
Section: Introductionmentioning
confidence: 98%
“…In more recent years, however, the reflection spectra of some Gefion family members were found to resemble that of H chondrites and basaltic achondrites (McGraw et al. ) and the age of the Gefion family may be older than required, 1103 ± 386 Ma according to Spoto et al. (), who did not include the initial velocity at ejection, however.…”
Section: Introductionmentioning
confidence: 99%
“…Gefion is the only known family with large members of L (as opposed to H and LL) chondrite composition (Vernazza et al 2014) and some asteroids found in the 3:1 meanmotion resonance, e.g., (355) Gabriella, (14470) Utra, and (1722) Goffin, have L chondrite-like spectra (Fieber-Beyer and Gaffey 2015). In more recent years, however, the reflection spectra of some Gefion family members were found to resemble that of H chondrites and basaltic achondrites (McGraw et al 2017) and the age of the Gefion family may be older than required, 1103 AE 386 Ma according to Spoto et al (2015), who did not include the initial velocity at ejection, however.…”
Section: Introductionmentioning
confidence: 99%